2019
DOI: 10.3390/genes10060474
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of a Stromal Vascular Fraction from Microfragmented Lipoaspirate Used in Osteoarthritis Cartilage Treatment and Its Lipoaspirate Counterpart

Abstract: Osteoarthritis (OA) is a degenerative joint disease accompanied by pain and loss of function. Adipose tissue harbors mesenchymal stem/stromal cells (MSC), or medicinal signaling cells as suggested by Caplan (Caplan, 2017), used in autologous transplantation in many clinical settings. The aim of the study was to characterize a stromal vascular fraction from microfragmented lipoaspirate (SVF-MLA) applied for cartilage treatment in OA and compare it to that of autologous lipoaspirate (SVF-LA). Samples were first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…We used the pairwise t-test for paired and subsequent measurements of the same patient or a knee. Within-individual variation was defined on the basis of the dGEMRIC error rates, which were based on previously published papers, and this indicated that the mean difference per region of interest between the two T1Gd measurements ranged from 3.7% to 6.8% [14,16,18]. Based on this, we defined the arbitrary change of 15% in subsequent measurements as clinically relevant, and considered this as the liminal value (on the basis of two standard deviations from the estimated error rate).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the pairwise t-test for paired and subsequent measurements of the same patient or a knee. Within-individual variation was defined on the basis of the dGEMRIC error rates, which were based on previously published papers, and this indicated that the mean difference per region of interest between the two T1Gd measurements ranged from 3.7% to 6.8% [14,16,18]. Based on this, we defined the arbitrary change of 15% in subsequent measurements as clinically relevant, and considered this as the liminal value (on the basis of two standard deviations from the estimated error rate).…”
Section: Discussionmentioning
confidence: 99%
“…The collected and processed final microfragmented adipose tissue product was transferred to several 10 mL syringes and injected intra-articularly (4-15 mL) into the index knee. Immunophenotyping of a stromal vascular fraction from microfragmented lipoaspirate was also done [16].…”
Section: Transplantation and Processing Of Microfragmented Adipose Timentioning
confidence: 99%
“…Another study included classifying and describing cell types contributing to the effect of treatment [ 207 ]. A stromal vascular fraction from lipoaspirate (SVF-LA) and stromal vascular fraction from microfragmented lipoaspirate (SVF-MLA) samples were characterized, and the following population phenotypes were identified within the CD45− fraction: endothelial progenitor cells (EPC), endothelial mature cells, pericytes, transitional pericytes, and supra adventitial-adipose stromal cells (SA-ASC).…”
Section: State-of-the-art Non-operative Therapeutic Considerationmentioning
confidence: 99%
“…As already underlined in our previous review, Lipogems ® is currently used within the clinic in several orthopedic contraindications, where intra-articular injections are used to for the management of knee, hip and shoulder osteoarthritic degeneration (more than 35000 patients over the world). Initiated more than three years ago, these results have now been confirmed in several case series [50,51], and prospective clinical studies with follow up [52,53], and the "regenerative" pathophysiological mechanism of Lipogems ® , when injected into the joint, have now been more carefully elucidated [54,55]. MFAT has also been demonstrated effective also in four patients with osteochondral lesions of the talus [56] who underwent to arthroscopic injection of MFAT of the osteochondral lesion after a first phase of microperforation of the cartilage.…”
Section: Orthopedic Surgerymentioning
confidence: 89%